A Work and systems study on devon garments - Belgira, John (College of Engineering, 1992)
The study focuses on the operations of a garments manufacturing firm. In particular, the group studied the production of jogging suits by an export-oriented company. With the aim of improving efficiency and raising productivity, the group observed and analyzed the company's operations and based on these, sought improvements through recommendations. Areas of interest to the group include the production process, the working conditions and systems and procedures. The group made observations on the day to day operations of the plant and also conducted interviews. Data were recorded to help the group identify potential problem areas. Problem areas identified by the group are the layout, the working conditions and the organizational set-up. The study showed an inefficient utilization of space and a hampering of workers' movements and functions leading to a longer production time. The group also found several fire hazards in the plant, as well as accident causing situations. The company set-up did not maximize functional responsibility. Changes proposed by the group include a change in the lay-out to maximize space and improve production time. To lessen the possibility of fires and accidents, the group suggests a change in the lighting system of the plant and an improvement of the plant's housekeeping. The group also suggests some organizational changes in the company's set-up to make operations more efficient. The recommendations made by the group reflect its view of effecting improvements at minimal cost and maximum savings and benefits.